Efficacy and Safety of 177Lu-PSMA-617 in Combination with Radical Prostatectomy and Bilateral Orchiectomy in Men with Castrate-Sensitive Metastatic Prostate Cancer: A Pilot Study - Amanollahi Soudmand, Saber; Hoseinzadeh, Samaneh; Moosavi, Maryam; Simforoosh, Nasser (Urology Journal, 2024)
Purpose: To investigate the efficacy and safety of 177Lu-PSMA-617 in combination with radical prostatectomy and bilateral orchiectomy in adult male patients with castrate-sensitive metastatic prostate cancer. Methods: This pilot study included 12 men with metastatic prostate cancer who underwent radical prostatectomy and received 177Lu-PSMA-617 in combination with hormonal therapy. The primary endpoint was the proportion of patients who achieved a PSA response, defined as a ≥ 50% reduction in PSA levels at first follow up from baseline. Secondary endpoints were the proportion of patients who achieved a PSA response, defined as a ≥ 50% reduction in PSA levels at the second follow up from the first one and progression in pain severity that was defined as an increase in score of 30% or greater from baseline without a decrease in analgesic use based on Brief Pain Inventory-short Form (PBI-SF). Results: The PSA levels of 9(75.0%) patients were reduced after the first course of 177Lu-PSMA-617, additional reduction was observed in 7(58.3%) patients after receiving the 2nd course of treatment. Of the 12 patients, 3(25.0%) achieved a PSA response (≥ 50% reduction in PSA levels) at first follow up visit and 3(25.0%) patients had PSA response at second follow up, 6 patients (50.%) had a pain response. The most common adverse events were Mouth dryness and fatigue, which were manageable with supportive care. Conclusion: This pilot study suggests that radical prostatectomy and hormonal therapy in combination with 177Lu-PSMA-617 is a safe and effective treatment option and may have a role in the management of select patients with castrate-sensitive metastatic prostate cancer. Further studies are needed to confirm these findings and determine the optimal use in this setting.